2011
DOI: 10.1017/s0022278x10000649
|View full text |Cite
|
Sign up to set email alerts
|

African Shenzhen: China's special economic zones in Africa

Abstract: This article examines recent Chinese efforts to construct a series of official economic cooperation zones in Africa. These zones are a central platform in China's announced strategy of engagement in Africa as ‘mutual benefit’. We analyse the background, motives and implementation of the zones, and argue that they form a unique, experimental model of development cooperation in Africa: market-based decisions and investment by Chinese companies are combined with support and subsidies from an Asian ‘developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(161 citation statements)
references
References 8 publications
3
156
0
2
Order By: Relevance
“…The foregoing challenges the conception of a homogenous China, and demonstrates that the motives of Chinese firms' engagement in Kenya are not limited to asset and resource seeking (Kurlandtzick, 2006;Drogendijk and Blomkvist, 2013). While Li et al (2013) have found that the Chinese acted to represent the interests of firms in the natural resource sector, our findings are consistent with Brautigan and Tang (2011) who found that the Chinese government's role in creating special economic zones in Africa was limited to the initial diplomatic deliberations, after which the companies became the main actors.…”
Section: Came To Kenya Because I Was Not Sure What the Economic Refsupporting
confidence: 82%
“…The foregoing challenges the conception of a homogenous China, and demonstrates that the motives of Chinese firms' engagement in Kenya are not limited to asset and resource seeking (Kurlandtzick, 2006;Drogendijk and Blomkvist, 2013). While Li et al (2013) have found that the Chinese acted to represent the interests of firms in the natural resource sector, our findings are consistent with Brautigan and Tang (2011) who found that the Chinese government's role in creating special economic zones in Africa was limited to the initial diplomatic deliberations, after which the companies became the main actors.…”
Section: Came To Kenya Because I Was Not Sure What the Economic Refsupporting
confidence: 82%
“…Moreover, while our focus was on trade, more research is warranted on the role of economic diplomacy in investment flows (Cheung et al 2012;, contracted engineering projects (Cheung et al 2014), the allocation of Special Economic Zones (Bräutigam and Tang 2011), or the promotion of the Renminbi as a world currency (Liao and McDowell 2015, forthcoming), among many other areas of China's growing economic engagement in the world. 1950 1955 1960 1965 1970 1975 1980 1985 1990 1995 2000 2005 2010 2015 Recognition of ROC (Taiwan …”
Section: Discussionmentioning
confidence: 99%
“…Legions of international consultants and development agencies have spent time and money on the matter. Asian countries with successful SEZs also provide technical expertise and financial support for African SEZ development as part of their bilateral development assistance (Bräutigam and Xiaoyang 2011).…”
Section: Sezs In Africamentioning
confidence: 99%